Authoritarian Actors and Strategic Digital Information Operations : The New Age of Manipulation - Ihsan Yilmaz; Shahram Akbarzadeh (Routledge, 2025)
This book explores the complex web of Strategic Digital Information Operations (SDIOs) – defined as deliberate efforts by state and non-state actors to manipulate public opinion and emotions using digital technologies – that intersect with political ambitions to create a complex environment ripe for manipulation.Drawing from extensive research and case studies, the book examines how actors ranging from authoritarian regimes to extremist groups such as ISIS, and even political entities in democratic countries, leverage digital platforms to further their agendas. As such, it provides a comprehensive overview of SDIOs, their evolving tactics, and implications for democracy, governance, and international relations. It examines the diverse tactics employed by these actors, from spreading half-truths and distractions to leveraging historical and religious narratives in the form of conspiracy theories or non-conspiracy narratives, aiming to control the discourse and shape the online environment to their advantage. This research challenges the conventional focus on disinformation, highlighting the shift toward more sophisticated and less discernible means of digital manipulation globally, and argues that SDIOs have become a pivotal tool for influencing public opinion, shaping political narratives, and even undermining democratic processes.This book will be of key interest to scholars, students, and practitioners in communications/media studies, political sociology, comparative politics, security studies, political science, and international politics.The Open Access version of this book, available at www.taylorfrancis.com, has been made available under a Creative Commons Attribution-Non Commercial-No Derivatives (CC-BY-NC-ND) 4.0 International license.